On flexural, wear and morphological properties of 3D printed almond skin powder reinforced PLA matrix. Issue 3 (3rd July 2022) - Singh, Rupinder; Kumar, Ranvijay; Singh, Mohit; Preet, Pawan
ABSTRACT: In past one decade, some studies have been reported on use of natural fibre-reinforced thermoplastic matrix such as polylactic acid (PLA)-based 3D-printed functional prototypes for biomedical applications. But hitherto little has been reported on the flexural, wear and morphological properties of almond skin powder–-reinforced PLA matrixbased 3D-printed functional prototypes prepared by fused filament fabrication (FFF) as biomedical scaffold/implant. In this study, the 3D-printed functional parts were subjected to flexural, wear and morphological investigations. The results suggested that maximum flexural strength at break and peak was observed as 57.38 MPa and 63.761 MPa, respectively (while printing with FFF at infill density 60%, infill angle 60° and infill speed 70 mm/s). The results are supported with the optical photomicrographs and surface topography analysis, which shows that there is relation between mechanical and surface properties of functional prototypes. The minimum surface roughness (Ra) 19.98 nm has been observed for 3D-printed flexural samples at proposed settings.